Polinef-MI Pelatihan Aplikasi Hot Potatoes dalam Pembuatan Instrumen Soal Inovatif bagi Guru Madrasah Aliyah Negeri Fakfak - Arridha, Riyadh; Andi Roy (Politeknik Negeri Fakfak, 2025)
Education is one of the basic needs in human life which can be said to be good if it is integrated with the needs and developments of the times. Information and communication technology has an important role in the world of education, especially in the learning process. One part of the learning process is evaluation activities. So far, conventional evaluation activities tend to be boring and not innovative. One of the things that can be done to overcome this problem is the development of innovative questions by utilizing information and communication technology (ICT). Therefore, the aim of this community service activity is to improve the ability of teachers in utilizing ICT at Madrasah AIiyah Negeri (MAN) Fakfak in making innovative question instruments using the Hot Potatoes application. This training activity uses lecture, discussion, question and answer and practice methods. Through this training, it is hoped that teachers will have the skills to create innovative question instruments using the Hot Potatoes application. This activity is also expected to improve teachers' abilities in the field of ICT in teaching. Apart from that, this activity is also expected to increase students' motivation in participating in learning evaluations due to innovation in the use of ICT in the learning evaluation process. The results of the questionnaire showed that the teachers were very enthusiastic about the activities carried out and helped them in developing a variety of innovative questions using the hot potatoes application with an average score of 89.78.